EFISIENSI TERMAL DESAIN SISTEM PEMANAS AIR ENERGI MATAHARI DENGAN VARIASI JUMLAH PIPA BESI - Rosalina Rosina Mirino; Kharl Hainz Yarama Rumbiak; Mujasam Mujasam (FMIPA Universitas Papua, 2022)
This study aims to determine the average value of hot water temperature and thermal efficiency that can be produced by using iron pipes as fluid collectors in the Solar Energy Water Heater design system. Collector pipes are made in three variations of 5, 7 and 9 pipes which are placed in a wooden box with transparent glass as a cover on the collector surface. The inside of the wooden box is lined with styrofoam and aluminum foil to reduce heat loss to the environment. Data were collected by observing and measuring the temperature of hot water with three variations of the number of pipes, each variation of the number of pipes carried out for three days. This water temperature measurement was carried out for 6 hours, from 10.20-16.30 WIT. The average maximum temperature produced for a total of 5 collector pipes is 59.70C, a total of 7 pipes is 63.70C, and a total of 9 collector pipes is 61.70C. The thermal efficiency value of the solar energy water heating system design for the number of 5 collector pipes is 96% , the number of 7 collector pipes is 97%, and the 9 collector pipes is 99%.